Pengaruh Kualitas Informasi dan Brand Image Terhadap Minat Beli Konsumen pada Produk iPhone Second di Semarang dengan Persepsi Konsumen sebagai Variabel Intervening - Arriana, Primarinha; Ervina , hawik; Meiriyanti, Rita (Fakultas Ekonomi dan Bisnis Universitas PGRI Semarang, 2025)
This study explores the impact of information quality and brand image on the purchase intention of consumers buying second-hand iPhones, considering consumer perception as an intervening variable. A total of 385 respondents who bought second-hand iPhones at PS Store Semarang participated in the research. The results show that brand image positively influences purchase intention, with a path coefficient of 0.116 and a p-value of 0.024. Brand image also significantly affects consumer perception, with a path coefficient of 0.339 and a p-value of 0.000. Conversely, information quality does not have a direct significant impact on purchase intention (path coefficient of 0.123, p-value of 0.099). However, it significantly affects consumer perception (path coefficient of 0.634, p-value of 0.000). Consumer perception significantly influences purchase intention, with a path coefficient of 0.723 and a p-value of 0.000. It serves as a crucial mediator between brand image and purchase intention (indirect effect of 0.245, p-value of 0.000) and between information quality and purchase intention (indirect effect of 0.458, p-value of 0.000). The model accounts for 89.8% of the variance in purchase intention and 91.0% in consumer perception, highlighting the importance of enhancing information quality and maintaining a strong brand image to boost consumer purchase intentions.